Experimental Test of the Effect of PCM Volume as Thermal Energy Storage Solar Power in Solar Cooking Units - Napitupulu, Richard A.M.; Peranginangin, Siwan E.A.; Siagian, Parulian (Jurnal Polimesin, 2023)
One solution that can be taken to reduce GHG emissions is to reduce consumption of fossil fuels and replace them with renewable energy sources. Indonesia is rich in renewable energy sources, and one that has potential to be developed is solar energy. In line with Indonesia's development into a developed country, energy consumption is increasing. One of the activities that contributes to the largest energy use is cooking. The need for energy for cooking in Indonesia is large because the population and households are very large, No. 4 in the world. Solar Cooker is an alternative to reduce the use of fossil or traditional energy for cooking activities. Previous research has shown how the performance of a Solar Cooker can be improved if it is integrated with PCM thermal energy storage, making it possible to speed up cooking time, cook with low solar intensity and even make it possible to cook at night. However, the quantitative influence of the number of PCMs in a solar cooker has not been specifically explained or studied. A low quantity of PCM results in reduced performance, while a high quantity will increase the thermal load, and thus overheating. This research tested 4 units of Simple Tube type Solar Cooker with different quantities of PCM for each unit. From the results of testing the Solar Cooker with the PCM thermal Energy Storage TEST with variations in PCM volume, it showed performance in storing heat for longer even in conditions of high rainfall day and night conditions. This is shown from all observation results during the 6 days of the experiment. As evidenced by the low ambient air temperature and high humidity, especially at night, the temperature drop in the cooking vessel water is quite low. This applies to every variant. From the experimental results, it can also be seen that variants number 1 and 3, especially number 3, have quite good performance, in absorbing heat and storing heat with an outer diameter of 350 mm